2019
DOI: 10.1002/tox.22879
|View full text |Cite
|
Sign up to set email alerts
|

Impact of zinc oxide nanoparticles on thioredoxin‐interacting protein and asymmetric dimethylarginine as biochemical indicators of cardiovascular disorders in gamma‐irradiated rats

Abstract: Nanoparticle is a microscopic particle that has been existed in a wide range of biotechnological purposes. Zinc oxide nanoparticles (ZnO‐NPs) have fewer environmental hazards and have shown positive impacts in the medical field. This work aimed to observe the effects of low and high doses of ZnO‐NPs on heart injury induced by ionizing radiation (IR). Animals were irradiated by 8 Gy of gamma rays and ZnO‐NPs (10 and 300 mg/Kg/day) were orally delivered to rats 1 hour after irradiation. Animals were dissected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…32 Symmetric dimethylarginine has changed in rats with cardiovascular disorders after gamma rays irradiation. 33 L-palmitoylcarnitine is not found to have a direct relationship with IR, but as a type of fatty acylation, palmitoylation plays an essential role in many biological processes, such as apoptosis and proliferation. 34 N-acetylornithine is identified as minor components of deproteinized plasma of humans, and 2-aminooctanoic acid is a fatty acid that modifies a lactoferricin B peptide to improve antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…32 Symmetric dimethylarginine has changed in rats with cardiovascular disorders after gamma rays irradiation. 33 L-palmitoylcarnitine is not found to have a direct relationship with IR, but as a type of fatty acylation, palmitoylation plays an essential role in many biological processes, such as apoptosis and proliferation. 34 N-acetylornithine is identified as minor components of deproteinized plasma of humans, and 2-aminooctanoic acid is a fatty acid that modifies a lactoferricin B peptide to improve antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the increase in mtROS in endothelial cells under I/R injury may also result from excessive inflammation response because myeloperoxidase (MPO) expression, a neutrophil infiltration marker, is upregulated in reperfused heart [101,102]. Increased thioredoxin-interacting protein (TXNIP) and a noticeable decline in the levels of thioredoxin 1 (Trx-1), thioredoxin reductase (TrxR), glutathione (GSH), catalase (CAT), and glutathione peroxidase (GPx) may also contribute to endothelial oxidative stress [103]. In order to attenuate oxidative stress in endothelial cells under I/R injury, several drugs or approaches have been developed.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Compared to the negative control and tris (2-chloroethy) phosphate (TCEP) alone, the binary mixture of PS-MPs and TCEP in that study induced the lowest activity in mice (Mus musculus). Rodent studies, however, have demonstrated alterations in SOD activity due to engineered nanoparticles exposure early in life or in adulthood [40,66,67]. Likewise, in the intestine of male marine medaka (Oryzias melastigma), chronic exposure to PS particles (10 µm) led to increased activity of SOD, while in females its activity was signi cantly decreased in ovaries [68].…”
Section: Discussionmentioning
confidence: 99%